Lost opportunities to prevent early onset type 2 diabetes mellitus after a pregnancy complicated by gestational diabetes - Bernstein, Judith A (BMJ Open Diabetes Res Care, 2016)
OBJECTIVES: Gestational diabetes mellitus (GDM) greatly increases the risk of developing diabetes in the decade after delivery, but few women receive appropriately timed postpartum glucose testing (PPGT) or a referral to primary care (PC) for continued monitoring. This qualitative study was designed to identify barriers and facilitators to testing and referral from patient and providers' perspectives. METHODS: We interviewed patients and clinicians in depth about knowledge, values, priorities, challenges, and recommendations for increasing PPGT rates and PC linkage. Interviews were coded with NVIVO data analysis software, and analyzed using an implementation science framework. RESULTS: Women reported motivation to address GDM for the health of the fetus. Most women did not anticipate future diabetes for themselves, and focused on delivery outcomes rather than future health risks. Patients sought and received reassurance from clinicians, and were unlikely to discuss early onset following GDM or preventive measures. PPGT barriers described by patients included provider not mentioning the test or setting it up, transportation difficulties, work responsibilities, fatigue, concerns about fasting while breastfeeding, and timing of the test after discharge from obstetrics, and no referral to PC for follow-up. Practitioners described limited communication among multiple care providers during pregnancy and delivery, systems issues, and separation of obstetrics from PC. CONCLUSIONS: Patients' barriers to PPGT included low motivation for self-care, structural obstacles, and competing priorities. Providers reported the need to balance risk with reassurance, and identified systems failures related to test timing, limitations of electronic medical record systems (EMR), lack of referrals to PC, and inadequate communication between specialties. Prevention of early onset has great potential for medical cost savings and improvements in quality of life.